2014
DOI: 10.19030/jber.v12i2.8526
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status, Religiosity, And Experience As A Predictor Of Ethical Awareness Among Accounting Professionals

Abstract: Many corporations and their accountants have taken ethics for granted. This oversight has led to the closing of companies such as Enron and (rho = -0.084, p = 0.226, n = 83)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…They will be perceived that the questionable accounting actions are unethical. The results of this study is similar to Vitell 2009), but different from the results of research Gorjidooz & Greenman ( 2012) and (Hickman, 2013). The result of hypothesis testing H2b shows regression coefficient on interaction of love of money and extrinsic religiosity is 0.032 and significant at p-value 0.020 ( Table 5).…”
Section: Resultscontrasting
confidence: 59%
“…They will be perceived that the questionable accounting actions are unethical. The results of this study is similar to Vitell 2009), but different from the results of research Gorjidooz & Greenman ( 2012) and (Hickman, 2013). The result of hypothesis testing H2b shows regression coefficient on interaction of love of money and extrinsic religiosity is 0.032 and significant at p-value 0.020 ( Table 5).…”
Section: Resultscontrasting
confidence: 59%
“…Single students had significantly higher moral sensitivity, which agrees with Razeghi et al [15], especially in the domain of moral courage. In contrast, Jafari Nadoushan et al [16] and Gorjidooz and Greenman [27] reported no significant relationship between behavioral skills and marital status.…”
Section: Discussionmentioning
confidence: 91%
“…Simply understanding the basics of the ethical thought process is not enough. At times there is a necessity to comprehend the basic principles of ethics on a higher level and to be able to extract a difference between ethical reasoning and the theory of that reasoning (Greenman, 2012).…”
Section: Theories Of Ethical Behaviormentioning
confidence: 99%